Fenomena “The Nuruls” Di Kota Depok. (Studi Fenomenologi Remaja Berhijab Di Kota Depok) - Sartika, Novia Dwi; Erlangga, Christhoper Yudha (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study examines the phenomenon of "The Nuruls" in Depok City, a group of hijab wearing teenage girls whose lifestyle negotiates between conservative values and modern social demands. The research aims to understand the social interactions of "The Nuruls" through a phenomenological approach and identify factors influencing their social interactions. Using a qualitative studi phenomenological method, this study involves 4 hijab-wearing teenage informants aged 15-22 years, selected through purposive sampling. The results show that "The Nuruls" form their own social reality through activities such as hanging out in cafes, listening to music, and adopting casual styles. Social interactions within this group create an intersubjective reality and collective identity that strengthens the formation of meaning and self-identity as hijab wearing teenagers different from general expectations. This phenomenon reflects the dynamics of hijab-wearing teenage girls' identity in the digital era, who strive to balance religious values with modern lifestyles, although it can sometimes lead to negative social interactions.